Lethal Necrotising Mediastinitis: A Rare but Critical Complication Post-Cervical Disc Arthroplasty - Soehadak, Faizal Ariffianto; Wardhana, Teddy Heri; Widhiyanto, Lukas (Scripta Medica, 2025)
Cervical disc arthroplasty is one of the common procedures for treating cervical degenerative disc disease. Anterior cervical disk arthroplasty is associated with a minimal complication rate, with documented infection rates ranging from 0.07 % to 1.6 %. This article reports on a lethal case of infection following cervical disc arthroplasty. A 42-year-old female presented with dysphagia and a sensation of choking just four weeks following cervical disc arthroplasty. Radiological examination showed soft tissue swelling and extensive subcutaneous emphysema, but no implant displacement, loosening, or subsidence was found. The patient underwent debridement surgery promptly; however, her condition deteriorated, ultimately leading to her demise—postoperative infections following cervical disc arthroplasty frequently present with ambiguous symptoms. The onset of these infections can range from several months to years. This article conveys the importance of recognising the signs of infection to facilitate early treatment for patients experiencing post-cervical disc arthroplasty infections.